Monitoring the Photothermal Reshaping of Individual Plasmonic Nanorods with Coherent Mechanical Oscillations - Scarpettini, Alberto (2018)
Light absorption in gold nanoparticles leads to metal heating that induces photothermal reshaping because of atomic surface diffusion at temperatures well below the gold melting point. In this work, we perform time-resolved experiments to measure the frequencies of the extensional coherent mechanical mode in single gold nanorods, as a monitor of the changes in their aspect ratio produced by this photoinduced reshaping. We show that photothermal reshaping always occurs in typical pump–probe experiments conducted in air even at low-excitation light irradiance and usually long measuring times. The reshaping effect can be reduced by a polymer coating, which allows faster heat dissipation from the nanoparticle to the environment.